The role of age and time horizon in affect–meaning relations - KEH, Jun Sheng (Institutional Knowledge at Singapore Management University, 2022)
Extant research has demonstrated robust positive relations between positive affect (PA) and meaning, although the strength of this relationship has been found to vary as a function of both chronological age and time horizon (Hicks et al., 2012). This can be explained by the Socioemotional Selectivity Theory (SST), which posits that both older adults and those with a limited time horizon (i.e., perceive less remaining in life) tend to focus on emotional goals over knowledge goals. In the current paper, I sought to extend SST’s findings to the level of activities by examining how chronological age, time horizon (both existing and manipulated), and one’s focus on emotional/knowledge goals influenced the strength of the relationship between the enjoyableness and meaningfulness of specific activities. These hypotheses were tested using an older (Study 1) and a younger adult sample (Study 2). Although none of the hypothesized relations were fully supported, interesting relations were uncovered through exploratory analyses that examined specific activities in terms of their experiential qualities and the joint effects of both positive (PA) and negative affect (NA) on activity-related meaning perceptions. In older adults, I found that for those with a limited time horizon, high-PA activities were less meaningful when also accompanied by NA. In contrast, for those with an expansive time horizon, high-PA activities remained meaningful even when accompanied by NA. In younger adults, I found that those who prioritized emotional goals experienced less meaning from uniformly negative activities compared to those who prioritized knowledge goals. Theoretical and practical implications of the current study are discussed.